Heterogeneity of stage IIIA endometrial carcinomas: implications for adjuvant therapy. Issue 3 (1st April 2005) - Slomovitz, B. M.; Ramondetta, L. M.; Lee, C. M.; Oh, J. C.; Eifel, P. J.; Jhingran, A.; Burke, T. W.; Gershenson, D. M.; Lu, K. H.
Abstract : The purpose of this study was to evaluate overall survival (OS) and determine prognostic subclassifications for stage IIIA endometrial cancer. Stage IIIA endometrial cancer patients treated at M.D. Anderson Cancer Center from 1989 to 2002 were reviewed. Clinical information was obtained from the medical record. Cox regression analyses were performed to evaluate the association of pathologic criteria and OS. Patients were divided into four groups based on this analysis: E1, endometrioid/pelvic cytology only; E2, endometrioid/adnexa ± serosal spread; NE1, nonendometrioid/pelvic cytology only; and NE2, nonendometrioid/adenexa ± serosal spread. Forty-nine patients were identified. By multivariate analysis, histology and extent of disease were the only factors associated with OS. Five-year OS in the four subgroups based on histology and extent of disease were: E1, 79%, E2, 65%, NE1, 64%, and NE2, 13%. Histologic subtype and extent of pelvic disease are the only prognostic factors associated with OS. Patients with endometrioid tumors and extent of pelvic disease limited to positive cytology had a favorable outcome, with or without adjuvant therapy. Future prospective clinical trials should consider subclassifying patients with stage IIIA disease to better evaluate the role of adjuvant therapy.